Leadership attribute profile of the coaches from Realmadrid Foundation Yogyakarta football school - Sulistiyono, Sulistiyono; Nugroho, Sigit; Prastyawan, Rifky Riyandi; Rahayu, Sundari Putri; Mahira, Rina; Rahmawati, Yuliana (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
The objective of this study is to identify the leadership characteristics exhibited by the coaches of RealMadrid Foundation Yogyakarta Football School. Research methodology employed was by descriptive quantitative study utilizing survey methods. The sampling technique used was exhaustive sampling, specifically included all five head coaches of the RealMadrid Foundation football school. Data collection technique used questionnaire by Google form completed by all 128 players. The data was examined by using descriptive statistics elaborated in percentages. The results' findings indicate that the technical skills category achieved the highest average score, with mean score 5.23 and corresponding percentage 87.16%. Ability of player's mental readiness demonstrates high level with mean score 5.18 and percentage of 86.34%. Bad attitude behavior is in score 5.12 and percentage of 85.28%. They possess medium ability to manage strategy for games scoring for 5.09 with percentage of 84.90%. Their goal-setting ability is below average with score 4.94 with 82.32% percentage. Lastly, their proficiency in managing physical training is relatively low, scoring 4.80 with a percentage of 80.08%. Coaches of RealMadrid Foundation Yogyakarta football school need to enhance their leadership skills in physical training and personality development. Leadership training offers an alternate approach to enhance the leadership skills of football coaches.